Combined liver and pancreas transplantation in two children with cystic fibrosis—First experience in Australia and New Zealand. (6th June 2018) - Shankar, Sahana; Bolia, Rishi; Hodgson, Alexandra; Bishop, Jonathan R.; Evans, Helen M.; Oliver, Mark R.
Abstract: We report the first two pediatric patients with CF who underwent successful combined liver‐pancreas transplantation in Australia and New Zealand for CF liver disease and CF‐related diabetes mellitus.